Facilitated Conversation: A Useful Tool in an Ethicist’s Toolbox - Hardy, Natalie; Nortje, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2020)
Soto’s syndrome is a rare form of genetic disorder, which is often non-life threatening. However, this case study will examine the case of a young lady with Soto’s syndrome who developed a pediatric cancer. The team and family had opposing goals of care. Ethical dilemmas in surrogate decision-making for mentally challenged individuals can often be resolved through facilitated conversation between the patient’s family and healthcare team.